Soapbox. The Stamp Magazine 89(5):29. (I. Das & G.V.A. Gee.) - Das, Indraneil (The Link House Group, 2023)
Mineral and gemstone-embedded stamps from Liechtenstein, produced by Hermann Sieger company are described.